Determinants Of Corporate Debt Ownership Structure In Malaysia - Mat Nor, Fauzias; Yatim, Yatim (Asian Academy of Management (AAM), 2000)
This paper examines the relationship between corporate debt ownership structure and several firm characteristics in Malaysia. Three dependent variables are used in testing this relationship namely the predominant proportion of long-term bank debts, long-term non-bank debts, and long-term public debts. The multiple regression analysis is used to examine the relationship amongst the dependent variables and the firm characteristics. The results demonstrate that the mean proportion of bank debt is higher than that of non-bank debt, but lower than that of public debt. The results also suggest negative relationship between bank debts with firm characteristics such as total assets, market to book value, and age of the firms. There is no significant relationship between characteristics of the firms, and the long-term non-bank debts and public debts.